Kedudukan Premisse dalam Anatomi Akta Notaris - Nadhia Apriana (Officium Notarium, 2023)
A notarial deed is an authentic deed made based on procedures and procedures that have been determined by law, Article 38 of the Notary Public Law (UUJP) provides the anatomy of a notarial deed which should consist of the opening part of the deed, the body of the deed and the closing of the deed, apart from what is confirmed in the article that there is a premise which has an important role similar to the rest of the deed anatomy though is not stated explicitly in the anatomy. Based on the issue, this research employs the normative or doctrinal method, in which the object is regulation with case study and statutory approaches. The primary legal materials in this research are statutory regulations and the secondary legal materials are books and journals. The results of this research indicate that the position of the premise in the anatomy of a notarial deed is located in the body of the deed between the comparison and the content of the deed which explains the statements of the parties and the facts relating to the deed to be made and secondly that the urgency of the position of the premise in the anatomy of the deed is to explains events that have occurred before the deed is made and needs to be included in writing in the deed. The author's recommendation in this research is to include the premise in the anatomy of the deed similar to the comparison and the contents of the deed as the legal basis for the premiseKey Word: Premise, Anatomy of a Notarial Deed AbstrakAkta notaris merupakan akta otentik yang dibuat berdasarkan prosedur dan tata cara yang telah ditentukan oleh undang-undang, Pasal 38 UUJP tentang antomi akta notaris terdiri dari awal akta, badan akta dan penutup akta, selain daripada yang ditegaskan dalam pasal tersebut bahwa terdapat premisse yang memiliki peran penting layaknya anatomi akta tersebut akan tetapi tidak dinyatakan tegas dalam anatomi. Berdasarkan permasalahan tersebut metode penelitian ini adalah normatif atau doktrinal yang objeknya adalah peraturan perundang-undangan dengan pendekatan kasus dan doktrin kemudian bahan hukum primer adalah peraturan perundang-undangan dan bahan hukum sekunder ialah buku serta jurnal. Hasil penelitian ini adalah kedudukan premisse dalam anatomi akta notaris adalah pada bagian badan akta antara komparisi dan isi akta yang menjelaskan tentang keterangan-keterangan para pihak maupun fakta-fakta yang berhubungan dengan akta yang hendak dibuat dan kedua bahwa urgensi kedudukan premisse dalam anatomi akta adalah untuk menerangkan kejadian yang telah terjadi sebelum dibuat akta dan perlu dicantumkan secara tertulis dalam akta. Saran penulis adalah premisse dimasukan dalam anatomi akta layaknya komparisi dan isi akta sehingga terwujud dasar hukum bagi premisse.Kata-kata Kunci: Premis, Anatomi Akta Notaris